Effects of Popular Diets on Anthropometric and Cardiometabolic Parameters: An Umbrella Review of Meta-Analyses of Randomized Controlled Trials. Issue 4 (14th February 2020) - Dinu, Monica; Pagliai, Giuditta; Angelino, Donato; Rosi, Alice; Dall'Asta, Margherita; Bresciani, Letizia; Ferraris, Cinzia; Guglielmetti, Monica; Godos, Justyna; Del Bo', Cristian; Nucci, Daniele; Meroni, Erika; et al.
ABSTRACT: The prevalence of overweight, obesity, and their related complications is increasing worldwide. The purpose of this umbrella review was to summarize and critically evaluate the effects of different diets on anthropometric parameters and cardiometabolic risk factors. Medline, Embase, Scopus, Cochrane Database of Systematic Reviews, and Web of Science, from inception to April 2019, were used as data sources to select meta-analyses of randomized controlled trials that examined the effects of different diets on anthropometric parameters and cardiometabolic risk factors. Strength and validity of the evidence were assessed through a set of predefined criteria. Eighty articles reporting 495 unique meta-analyses were examined, covering a wide range of popular diets: low-carbohydrate ( n  = 21 articles), high-protein ( n  = 8), low-fat ( n  = 9), paleolithic ( n  = 2), low-glycemic-index/load ( n  = 12), intermittent energy restriction ( n  = 6), Mediterranean ( n  = 11), Nordic ( n  = 2), vegetarian ( n  = 9), Dietary Approaches to Stop Hypertension (DASH) ( n  = 6), and portfolio dietary pattern ( n  = 1). Great variability in terms of definition of the intervention and control diets was observed. The methodological quality of most articles ( n  = 65; 81%), evaluated using the "A MeaSurement Tool to Assess systematic Reviews-2" questionnaire, was low or critically low. The strength of evidence was generally weak. The most consistent evidence was reported for the Mediterranean diet, with suggestive evidence of an improvement in weight, BMI, total cholesterol, glucose, and blood pressure. Suggestive evidence of an improvement in weight and blood pressure was also reported for the DASH diet. Low-carbohydrate, high-protein, low-fat, and low-glycemic-index/load diets showed suggestive and/or weak evidence of a reduction in weight and BMI, but contrasting evidence for lipid, glycemic, and blood pressure parameters, suggesting potential risks of unfavorable effects. Evidence for paleolithic, intermittent energy restriction, Nordic, vegetarian, and portfolio dietary patterns was graded as weak. Among all the diets evaluated, the Mediterranean diet had the strongest and most consistent evidence of a beneficial effect on both anthropometric parameters and cardiometabolic risk factors. This review protocol was registered at www.crd.york.ac.uk/PROSPERO/ as CRD42019126103.